Kepadatan dan Pola Persebaran Pauh Kijang (Irvingia malayana Oliv.) pada Habitat Orang Utan di Taman Nasional Gunung Palung Provinsi Kalimantan Barat - Siti Nurbaiti; Irwan Lovadi; Rafdinal Rafdinal (Bioscientist : Jurnal Ilmiah Biologi, 2022)
Gunung Palung National Park is one of the orangutan habitats on the island of Borneo. Based on previous research, it was reported that the Kijang Pauh plant (Irvingia malayana Oliv.) grows in this conservation area. Currently, research related to plant ecology is still very limited. This study aims to determine the density and distribution pattern of the Kijang Pauh plant. Data collection was carried out from July to August 2021 in three types of orangutan habitat, namely: sandy rock habitat, alluvial habitat, and fresh water habitat. The type of research used is descriptive quantitative, where the data is presented in tabular form. Data collection was carried out by making plots measuring 50 m x 20 m with random sampling method in three types of habitat. The results showed that the density of Irvingia malayana in sandstone, alluvial, and freshwater swamp habitats was 18 individuals/ha, 10 individuals/ha, and 12 individuals/ha, respectively. The distribution pattern of Irvingia malayana in the three habitats is even or uniform. Based on the research results that have been obtained, it can be concluded that the highest density values are found in sandstone habitats, and the lowest density values are found in alluvial areas with an even or uniform distribution pattern.